Weaving an innovation network from the middle-out: the case of the renewable energy ecosystem - Tali Zohar; Yael Parag; Ofira Ayalon (Energy, Sustainability and Society, 2022)
Abstract Background Renewable energy (RE) systems are becoming a central component of the clean energy transition and are often seen as the way to combat climate change. Their establishment requires innovation, investments, and deployment policies for emerging technologies. Governments around the world are increasingly trying to create and support the energy-tech and climate-tech innovation ecosystems in their attempt to promote an innovation-supporting environment. However, energy innovation policies are often aligned with the dichotomous notion of technology-push and market-pull and overlook the social, political, and cultural contexts in which RE innovative technologies are embedded, and the multiple actors and interactions that are associated with their development. By combining the Middle-Out Perspective (MOP) and innovation literature, this paper argues that an innovation ecosystem could be weaved from the middle-out. Methods This paper analyzes the case of ‘Eilat-Eilot Renewable Energy Initiative’ and Israel’s RE innovation ecosystem creation through the lens of the MOP and applies a socio-technical interpretation to the push and pull terminology. Process tracing methodology was applied to trace a sequence of events to determine whether an actor was pushed or pulled, the formation of a network of actors, and its evolvement to an energy innovation ecosystem from the middle-out. Data for the analysis were collected from interviews, policy papers, media articles, and Governmental decisions. Results The analysis demonstrates how middle actors push the implementation of RE technologies in Israel, and at the same time pull decision-makers and other middle actors to promote the low carbon transition. The push and pull forces and the interactions between actors lead to the engagement of new stakeholders in the innovation network, the adoption of more ambitious RE targets and supporting policies, and the creation of an effective RE innovation ecosystem. Conclusions This paper uses the MOP as an analytical framework and the push and pull terminology to demonstrate how a middle actor initiates and develops an actor-network by interacting with other actors. As this network broadens, it forms an effective innovation ecosystem. A network of actors has the potential to lead change, provide innovative ideas, initiate research, encourage investments, create employment possibilities, and promote regional sustainable development.